1972
DOI: 10.1080/00288233.1972.10421635
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early weaning on the concentrations of non-esterified fatty acids and glucose in the plasma of lambs

Abstract: Non-esterified fatty acids (NEFA) and glucose concentrations in the plasma of 9 lambs weaned from 3.5 to 9.5 weeks of age were compared with the concentrations found in 2 lambs suckling the ewe. Lambs weaned at 3.5 weeks had markedly elevated plasma NEFA concentrations for up to 3 weeks after weaning. A similar trend was apparent for 2 days after lambs were weaned at 5.5 weeks of age. There was a highly significant negative correlation between plasma NEFA and energy intake in these groups of lambs for 30 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As a result of calculations made from the partition of energy intake between maintenance requirement, protein and fat deposition and heat production, Black (1974) concluded that these observations can be largely explained by a decrease in energy intake associated with weaning. Fennessy, Woodlock & Jagusch (1972) found a rise in plasma non-esterified fatty acids, indicating increased mobilization of body fat, in lambs weaned from the ewe at 3-5 and 5-5 weeks of age (body weights 13-15 kg) but no rise in lambs weaned at 7-5 and 9-5 weeks of age (18 and 33 kg body weight respectively). The former lambs were in the transition phase of rumen development (Wardrop & Coombe, 1961) and could be compared with lambs in the present experiment in which a 2-week period of exposure to solid food and rumen microbes prior to the complete withdrawal of milk was probably not sufficient to establish a fully functional ruminant digestive tract.…”
Section: Discussionmentioning
confidence: 86%
“…As a result of calculations made from the partition of energy intake between maintenance requirement, protein and fat deposition and heat production, Black (1974) concluded that these observations can be largely explained by a decrease in energy intake associated with weaning. Fennessy, Woodlock & Jagusch (1972) found a rise in plasma non-esterified fatty acids, indicating increased mobilization of body fat, in lambs weaned from the ewe at 3-5 and 5-5 weeks of age (body weights 13-15 kg) but no rise in lambs weaned at 7-5 and 9-5 weeks of age (18 and 33 kg body weight respectively). The former lambs were in the transition phase of rumen development (Wardrop & Coombe, 1961) and could be compared with lambs in the present experiment in which a 2-week period of exposure to solid food and rumen microbes prior to the complete withdrawal of milk was probably not sufficient to establish a fully functional ruminant digestive tract.…”
Section: Discussionmentioning
confidence: 86%
“…This can likely be explained by a relatively lower ME intake in calves after weaning, as the progressive increase in SF intake was limited by their intake capacity. Similarly, an increase in fat metabolism (and thus NEFA levels) to meet energy requirements after weaning was also seen in early-weaned lambs (Fennessya et al, 1972).…”
Section: Postprandial Responses Of Plasma Glucose Insulin and Nefamentioning
confidence: 92%
“…This has been associated with a reduction in fat levels immediately following weaning due to fat mobilisation (Fennessy et al 1972) and an increased requirement of energy for protein deposition in Receh'ed 20 May 1980 The possible effects on lamb growth and carcass composition of varying both lamb weaning and slaughter ages have not been clearly established. The present experiments were designed to provide such information.…”
Section: Introductionmentioning
confidence: 97%